If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -93 = 8(k + -4) + 3 Reorder the terms: -93 = 8(-4 + k) + 3 -93 = (-4 * 8 + k * 8) + 3 -93 = (-32 + 8k) + 3 Reorder the terms: -93 = -32 + 3 + 8k Combine like terms: -32 + 3 = -29 -93 = -29 + 8k Solving -93 = -29 + 8k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-8k' to each side of the equation. -93 + -8k = -29 + 8k + -8k Combine like terms: 8k + -8k = 0 -93 + -8k = -29 + 0 -93 + -8k = -29 Add '93' to each side of the equation. -93 + 93 + -8k = -29 + 93 Combine like terms: -93 + 93 = 0 0 + -8k = -29 + 93 -8k = -29 + 93 Combine like terms: -29 + 93 = 64 -8k = 64 Divide each side by '-8'. k = -8 Simplifying k = -8
| 5x+8x=65 | | -101=1+3(2-6p) | | -2+5(-7n+7)=313 | | -55=8+7x | | 3x+5=13x | | -2+7(7-2n)=159 | | 8y-6=2/3(6y+15) | | 5r-6(5r-5)=-170 | | 6k-6(1-4k)=6k-30 | | -7(2n+5)-3n=-171 | | 12n-3=8(n-4)+5n | | 5-2y=4y-11 | | 3c-5=2x | | -4x^2-24x=36 | | a+5d=17a+2d=8 | | 3t^2+14n-5=0 | | 3t^2+14-5=0 | | a+5d=17 | | -3-6x=-3x+3(x-3) | | x^2+18x+145=0 | | (x+3)2=16 | | 4(a-3)=3-(a+5) | | 8y+3(y-7)=5(y+1)-3 | | 0.50x+0.80(50)=0.25(134) | | -6(-5+2r)=66 | | -5y+4=-2(4y+4) | | -3x+3y=8 | | 14=x-(-7) | | -2.9m+0.6-1.5m=8.4-4.4m-7.8 | | 12y-36=15y | | -4x^2-24x=-36 | | p^2+10=8p |